Poetic Healing of the Collective Black Mind: The Example of Langston Hughes and Maya Angelou. - Ogbaa, Kalu (2003)
Keywords: dept.eng; faculty_collection; sabbatical_report

The Nigerian Americans - Ogbaa, Kalu (New Americans (Westport, Conn.), 2003)
Keywords: Nigerian Americans; Immigrants; Social conditions; United States; Nigerian Americans; dept.eng; faculty_collection

Gleanings: Old Poems, New Poems - Shipley, Vivian (Louisiana Literature Press, 2003)
Keywords: award_winner; dept.eng; faculty_collection

Corvus: Poems - Sonnenschein, Dana (Wind, 2003)
Fisher-Wirth, Ann W. Trinket poems.
Keywords: Corvus; Poetry; dept.eng; faculty_collection

The misunderstood discipline of composition studies [3] - Hood, C.L. (Chronicle of Higher Education, 2003)
Keywords: dept.eng; ⛔ No DOI found

Illusions of a public, locations of conflict: Feeling like populace in William Dean Howells' A Hazard of New Fortunes - Stretch, C. (American Literary Realism, 2003)
Keywords: dept.eng; ⛔ No DOI found